2011
DOI: 10.5483/bmbrep.2011.44.10.674
|View full text |Cite
|
Sign up to set email alerts
|

Essential role of tryptophan residues in toxicity of binary toxin from Bacillus sphaericus

Abstract: Bacillus sphaericus produces mosquito-larvicidal binary toxin composed of BinA and BinB. While BinB is expected to bind to a specific receptor on the cell membrane, BinA interacts to BinB or BinB receptor complex and translocates into the cytosol to exert its activity via unknown mechanism. To investigate functional roles of aromatic cluster in BinA, amino acids at positions Y213, Y214, Y215, W222 and W226 were substituted by leucine. All mutant proteins were highly produced and their secondary structures were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 23 publications
1
6
1
Order By: Relevance
“…Pore formation by the Bin components has been demonstrated by patch clamp experiments on Culex quinquefasciatus cells . Similarly, previous studies have shown that both BinA and BinB components were able to permeabilize planar lipid bilayer and receptor‐free large unilamellar phospholipid vesicles . Both BinA and BinB components could insert into lipid monolayers, and conformational changes of both BinA and BinB were observed upon membrane association .…”
Section: Introductionsupporting
confidence: 56%
“…Pore formation by the Bin components has been demonstrated by patch clamp experiments on Culex quinquefasciatus cells . Similarly, previous studies have shown that both BinA and BinB components were able to permeabilize planar lipid bilayer and receptor‐free large unilamellar phospholipid vesicles . Both BinA and BinB components could insert into lipid monolayers, and conformational changes of both BinA and BinB were observed upon membrane association .…”
Section: Introductionsupporting
confidence: 56%
“…Given that L. sphaericus presents a tryptophan operon, this bacterium has the ability to synthesize tryptophan amino acid [11,23,38], which is one of the precursors to indole acetic acid [39,40]. In this sense, results showed that indole acetic acid could be determined directly from soil samples without the addition of tryptophan.…”
Section: Indole Acetic Acid Productionmentioning
confidence: 99%
“…BinA, BinB and Cry49Aa1 do contain an occurrence of the QxW motif in the β-sheet core of the C-terminal domain as does Cry35Ab1 although this occurrence of the motif is absent from the much more closely-related Cry35Aa1 sequence. In BinA, substitution of Trp222 in this feature, equivalent to Trp211 of Cry35Ab1, results in loss of activity although the protein is still able to permeabilize liposomes [63]. Ricin-B-like lectin repeats were also noted in the 41.9 kDa B. thuringiensis protein [51] although there are no QxW motifs in this protein.…”
Section: Resultsmentioning
confidence: 99%